ANALYSIS ON PROGRESS AND FUTURE DIRECTIONS ONHYDROLOGIC MODELING - B, Sangeethavani (International Journal of Psychosocial Rehabilitation, 2016)
An overview of hydrologic modeling’s past and future is presented in this paper, which analyses the advances made in hydrologic modelling since computer technology was introduced. It is possible to track the advancements in hydrology by examining the changes in data collecting and processing, conceptual frameworks, interdisciplinary collaboration, computational and analytical methods, and models and the results produced by those models and those methods. New data gathering and computation methods are predicted to assist hydrology by increasing integration with technical and non-technical disciplines and by increasing the usage of information technology resources. That’s why issues like food and water safety, energy security, public health, ecosystem stability, and sustainable development will all be impacted by hydrology in the twenty-first century .